Development, genetic mapping and QTL association of cotton PHYA, PHYB, and HY5-specific CAPS and dCAPS markers. Issue 1 (December 2016) - Kushanov, Fakhriddin; Pepper, Alan; Yu, John; Buriev, Zabardast; Shermatov, Shukhrat; Saha, Sukumar; Ulloa, Mauricio; Jenkins, Johnie; Abdukarimov, Abdusattor; Abdurakhmonov, Ibrokhim
Abstract Background Among SNP markers that become increasingly valuable in molecular breeding of crop plants are the CAPS and dCAPS markers derived from the genes of interest. To date, the number of such gene-based markers is small in polyploid crop plants such as allotetraploid cotton that has A- and D-sub-genomes. The objective of this study was to develop and map new CAPS and dCAPS markers for cotton developmental-regulatory genes that are important in plant breeding programs. Results Gossypium hirsutum andG. barbadense, are the two cultivated allotetraploid cotton species. These have distinct fiber quality and other agronomic traits. Using comparative sequence analysis of characterized GSTs of thePHYA1, PHYB, andHY5 genes ofG. hirsutum andG. barbadense onePHYA1 -specificMbo I/Dpn II CAPS, onePHYB -specificAlu I dCAPS, and oneHY5 -specificHinf I dCAPS cotton markers were developed. These markers have successfully differentiated the two allotetraploid genomes (AD1 and AD2 ) when tested in parental genotypes of 'Texas Marker-1' ('TM-1'), 'Pima 3–79' and their F1 hybrids. The genetic mapping and chromosome substitution line-based deletion analyses revealed thatPHYA1 gene is located in A-sub-genome chromosome 11, PHYB gene is in A-sub-genome chromosome 10, andHY5 gene is in D-sub-genome chromosome 24, on the reference 'TM-1' x 'Pima 3–79' RIL genetic map. Further, it was found that genetic linkage map regions containing phytochrome andHY5 -specific markers were associated with major fiber quality and flowering time traits in previously published QTL mapping studies. Conclusion This study detailed the genome mapping of three cotton phytochrome genes with newly developed CAPS and dCAPS markers. The proximity of these loci to fiber quality and other cotton QTL was demonstrated in two A-subgenome and one D-subgenome chromosomes. These candidate gene markers will be valuable for marker-assisted selection (MAS) programs to rapidly introgressG. barbadense phytochromes and/orHY5 gene (s) intoG. hirsutum cotton genotypes or vice versa.